Green and environmentally friendly alkali-activated gelling material and preparation method thereof
By mixing waste granite stone powder, blast furnace slag, metakaolin and urban solid waste incineration base ash with alkaline exciters, alkali-excited gelling materials with high mechanical properties and environmental protection characteristics are prepared, which solves the problems of high carbon dioxide emissions and energy consumption of existing gelling materials in the production process, and achieves the efficient utilization and environmental protection goals of waste.
Patent Information
- Application Number
- CN202310138382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-02-20
AI Technical Summary
The existing cementitious materials need to use cement, lime and other raw materials during the production process, resulting in high carbon dioxide emissions and energy consumption, and low waste utilization, affecting environmental protection and resource conservation.
By mixing the waste granite stone powder, blast furnace slag, metakaolin and urban solid waste incineration bottom ash in a specific proportion and reacting with alkaline exciters, alkali excitation gelling materials with high mechanical properties and environmental protection characteristics are prepared.
This method not only reduces dependence on raw materials such as cement and lime, reduces carbon dioxide emissions and energy consumption, but also improves waste utilization, forming gelled materials with good working performance and high mechanical properties, which have high economic and environmental benefits.
Smart Images

Figure BDA0004086771030000071 
Figure BDA0004086771030000081 
Figure BDA0004086771030000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a green and environment-friendly alkali-activated gelling material and a preparation method thereof. Background Art
[0002] In many cities in my country, the workload of building, renovating and repairing pipelines is very large, and urban roads are frequently excavated. Traditional trench backfill materials generally use natural graded sand and gravel or trench excavation earth and stone. Due to the narrow space of the pipeline trench, it is difficult to compact the fill, which often causes road surface settlement after opening to traffic, affecting the formation quality and generating secondary maintenance costs. Cementitious materials can be used to fill the trench space without compaction, reducing the compaction and compaction density inspection processes, and have many advantages such as convenient construction, economy, and environmental protection; and cementitious materials can also be used in mine backfilling and other aspects, with high practical application value. However, existing cementitious materials usually require the use of raw materials such as cement and lime, and the production of these raw materials is accompanied by a large amount of carbon dioxide emissions and high energy consumption, which is not conducive to environmental protection and energy conservation.
[0003] At the same time, in industrial production and urban life, the generation of a large amount of waste will also cause environmental pollution. For example, in the process of granite mining and processing, a large amount of granite waste is discarded at will. If the waste granite powder is simply piled up, it will not only waste resources, but also occupy a large amount of land and cause serious secondary pollution to the environment. When smelting pig iron, if the blast furnace slag discharged from the blast furnace cannot be effectively utilized, it will also affect the environment and cause waste of resources. The accumulation of municipal solid waste incineration bottom ash will also cause environmental pollution, and the municipal solid waste incineration bottom ash will produce serious foaming and expansion when encountering a strong alkaline environment, causing the municipal solid waste incineration bottom ash cementitious material to expand and deform, resulting in a sharp drop in the mechanical properties of the material, and it cannot be used in engineering practice. If the above-mentioned waste can be used in the preparation of cementitious materials, it can not only reduce the use of cement and lime in cementitious materials, but also improve the utilization rate of waste, which has a high research value.
[0004] The patent with publication number CN102887692A provides a method for preparing concrete using granite chips with high stone powder content. The patent replaces the cementitious material with part of the stone powder contained in the high stone powder content stone chips, and uses the secondary hydration reaction of the mineral admixture to wrap the stone powder in the secondary hydration product, thereby using the secondary hydration product to improve the strength of the concrete. However, this method still requires the use of a large amount of cement, and the proportion of stone powder replacing cementitious materials is low, and the utilization rate of stone powder is not high. The patent with publication number CN114315188A provides a process for preparing alkali-activated cementitious materials for the treatment of waste incineration bottom ash. This method eliminates the defect of bottom ash foaming and expansion when it encounters alkali by calcining and melting pretreatment and alkali aging pretreatment of the bottom ash. However, this method is not only cumbersome and complex in process, but also brings higher energy consumption in the calcining and melting treatment process, and also requires a large amount of alkali activator for aging treatment, which increases the treatment cost.
[0005] In view of this, it is necessary to design an improved green and environmentally friendly alkali-activated gelling material and a preparation method thereof to solve the above problems. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a green and environmentally friendly alkali-activated cementitious material and a preparation method thereof, by mixing waste granite powder with blast furnace slag, kaolin and municipal solid waste incineration bottom ash in a specific proportion, while making full use of the solid waste materials and utilizing the synergistic effect between the solid waste materials, to improve the performance of the cementitious material, and to alleviate the expansion and deformation of the municipal solid waste incineration bottom ash, thereby forming a cementitious material with better working performance and higher mechanical properties.
[0007] To achieve the above object, the present invention provides a green and environmentally friendly alkali-activated gelling material, which comprises the following components by mass fraction:
[0008] Waste granite powder 25.5% to 52%, blast furnace slag 16% to 37.5%, metakaolin 10% to 27%, municipal solid waste incineration bottom ash 10% to 20%, alkaline activator 5% to 10%.
[0009] As a further improvement of the present invention, the waste granite powder contains the following components by mass fraction:
[0010] Na2O 6% ~ 10%, MgO 0.2% ~ 0.8%, Al2O3 15% ~ 20%, SiO2 60% ~ 70%, Fe2O31% ~ 1.5%, K2O 4% ~ 5%.
[0011] As a further improvement of the present invention, the blast furnace slag contains the following components by mass fraction:
[0012] Na2O 0.1%~0.5%, MgO 4%~8%, Al2O310%~20%, SiO20%~40%, SO31.5%~3%, CaO 30%~50%, K2O 0.5%~1%, Fe2O30.2%~0.6%, TiO20.6%~1.2%, MnO 0.5~1%.
[0013] As a further improvement of the present invention, the metakaolin contains the following components by mass fraction:
[0014] Na2O 0.02% ~ 1%, MgO 0.1% ~ 0.4%, Al2O3 40% ~ 60%, SiO2 40% ~ 60%, CaO 0.1% ~ 0.5%.
[0015] As a further improvement of the present invention, the bottom ash from the incineration of municipal solid waste contains the following components by mass fraction:
[0016] Na2O 1%~3%, MgO 1%~3%, Al2O35%~15%, SiO215%~25%, P2O51.5%~3.5%, SO31%~3%, CaO 30%~50%, Fe2O36%~12%, Ti2O 1.5%~35%.
[0017] As a further improvement of the present invention, the alkaline activator is one of sodium hydroxide and water glass, or a combination of the two.
[0018] To achieve the above object, the present invention also provides a method for preparing the green and environmentally friendly alkali-activated gelling material, comprising the following steps:
[0019] S1. Mixing waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash according to a predetermined ratio, and fully ball-milling to obtain an admixture;
[0020] S2. Mixing the admixture with the alkaline activator according to a predetermined ratio to obtain a gelling material.
[0021] As a further improvement of the present invention, in step S1, the specific surface area of the admixture obtained after sufficient ball milling is greater than 600m 2 / kg.
[0022] As a further improvement of the present invention, after the cementitious material obtained in step S2 is mixed with standard sand and water and naturally cured, its 3d compressive strength is 4-12MPa, 7d compressive strength is 7-20MPa, 28d compressive strength is 8-35MPa, 3d flexural strength is 0.5-4MPa, 7d flexural strength is 1-5MPa, and 28d flexural strength is 1.5-6MPa.
[0023] As a further improvement of the present invention, the mass ratio of the cementitious material to the standard sand is 1:3, and the water-cement ratio of water to the cementitious material is 1:2.
[0024] The beneficial effects of the present invention are:
[0025] 1. The green and environmentally friendly alkali-activated cementitious material provided by the present invention uses a specific proportion of waste granite powder and blast furnace slag, metakaolin, municipal solid waste incineration bottom ash and alkaline activator as raw materials, while fully utilizing the solid waste materials and effectively utilizing the synergistic effect between the various solid waste materials, thereby preparing a cementitious material with better working performance and higher mechanical properties in a simple way and at a lower cost, and has higher economic and environmental benefits.
[0026] 2. The present invention not only greatly increases the amount of waste granite powder that is usually difficult to be effectively utilized by designing the ratio between waste granite powder and blast furnace slag, metakaolin, municipal solid waste incineration bottom ash and alkaline activator, but also can utilize the pore-filling effect of the waste granite powder to significantly improve the performance of metakaolin and blast furnace slag-based alkali-activated materials, while improving the working performance and mechanical properties of cementitious materials, but also helps to reduce the amount of alkali activator. In actual application, the hydrophobicity of the waste granite powder can also be used to reduce the water demand of the cementitious materials, thereby reducing production costs; at the same time, the addition of waste granite powder can also effectively alleviate the expansion and deformation of municipal solid waste incineration bottom ash in an alkaline environment, providing a simpler and more efficient way for the application of municipal solid waste incineration bottom ash.
[0027] 3. In the green and environmentally friendly alkali-activated cementitious material provided by the present invention, the waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash mixed in a specific proportion can dissolve a certain amount of silicon and aluminum under the action of the corresponding alkaline activator to generate hydrated silicate, zeolite-like products and the like, thereby producing higher strength. Based on this, the cementitious material provided by the present invention does not need to add raw materials such as cement and lime to achieve the required mechanical properties, and compared with the conventional cementitious materials produced using raw materials such as cement and lime, the emission of carbon dioxide and energy consumption are greatly reduced; and the waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash consumed in large quantities in the cementitious material provided by the present invention effectively avoid the waste of resources, while solving the pollution problem of these solid wastes to the environment, and the raw material acquisition cost is low, the preparation process is simple, and it can meet the needs of actual production and application. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below in conjunction with specific embodiments.
[0029] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0030] To achieve the above object, the present invention provides a green and environmentally friendly alkali-activated gelling material, which comprises the following components by mass fraction:
[0031] Waste granite powder 25.5% to 52%, blast furnace slag 16% to 37.5%, metakaolin 10% to 27%, municipal solid waste incineration bottom ash 10% to 20%, alkaline activator 5% to 10%.
[0032] The waste granite powder contains the following components by mass fraction:
[0033] Na2O 6% ~ 10%, MgO 0.2% ~ 0.8%, Al2O3 15% ~ 20%, SiO2 60% ~ 70%, Fe2O31% ~ 1.5%, K2O 4% ~ 5%.
[0034] The blast furnace slag contains the following components by mass fraction:
[0035] Na2O 0.1%~0.5%, MgO 4%~8%, Al2O310%~20%, SiO20%~40%, SO31.5%~3%, CaO 30%~50%, K2O 0.5%~1%, Fe2O30.2%~0.6%, TiO20.6%~1.2%, MnO 0.5~1%.
[0036] The metakaolin contains the following components by mass fraction:
[0037] Na2O 0.02% ~ 1%, MgO 0.1% ~ 0.4%, Al2O3 40% ~ 60%, SiO2 40% ~ 60%, CaO 0.1% ~ 0.5%.
[0038] The municipal solid waste incineration bottom ash contains the following components by mass fraction:
[0039] Na2O 1%~3%, MgO 1%~3%, Al2O35%~15%, SiO215%~25%, P2O51.5%~3.5%, SO31%~3%, CaO 30%~50%, Fe2O36%~12%, Ti2O 1.5%~35%.
[0040] The alkaline activator is one of sodium hydroxide and water glass or a combination of the two.
[0041] The present invention also provides a method for preparing the green and environmentally friendly alkali-activated gelling material, comprising the following steps:
[0042] S1. Mixing waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash according to a predetermined ratio, and fully ball-milling to obtain an admixture;
[0043] S2. Mixing the admixture with the alkaline activator according to a predetermined ratio to obtain a gelling material.
[0044] In step S1, the specific surface area of the admixture obtained after sufficient ball milling is greater than 600m 2 / kg.
[0045] After the cementitious material obtained in step S2 is mixed with standard sand and water and naturally cured, its 3d compressive strength is 4-12MPa, 7d compressive strength is 7-20MPa, 28d compressive strength is 8-35MPa, 3d flexural strength is 0.5-4MPa, 7d flexural strength is 1-5MPa, and 28d flexural strength is 1.5-6MPa.
[0046] The mass ratio of the cementitious material to the standard sand is 1:3, and the water-cement ratio of water to the cementitious material is 1:2.
[0047] The green and environmentally friendly alkali-activated gelling material and the preparation method thereof provided by the present invention are described below in conjunction with specific embodiments and comparative examples.
[0048] Example 1
[0049] This embodiment provides a green and environmentally friendly alkali-activated gelling material, which comprises the following components by mass fraction:
[0050] Waste granite powder: 25.5%
[0051] Blast furnace slag: 34%
[0052] Metakaolin: 25.5%
[0053] Municipal solid waste incineration bottom ash: 10%
[0054] Alkaline activator water glass: 5%
[0055] In this embodiment, the chemical composition of the waste granite powder is as follows:
[0056] Na2O: 8.46%; MgO: 0.46%; Al2O3: 18.97%; SiO2: 64.66%; Fe2O3: 1.17%; K2O: 4.55%.
[0057] The chemical composition of blast furnace slag is as follows:
[0058] Na2O: 0.316%; MgO: 5.66%; Al2O3: 15.7%; SiO2: 29.9%; P2O5: 0.0116%; SO3: 2.26%; CaO: 43.1%; Cl: 0.0052%; K2O: 0.778 %; Fe2O3: 0.400%; CuO: 0.0079%; TiO2: 0.901%; BaO: 0.129%; MnO: 0.701%; Rb2O: 0.0059%; SrO: 0.0785%; Y2O3: 0.0113%.
[0059] The chemical composition of metakaolin is as follows:
[0060] Na2O: 0.06%; MgO: 0.22%; Al2O3: 48.23%; SiO2: 50.07%; CaO: 0.24%; Fe2O3: 0.0012%.
[0061] The chemical composition of municipal solid waste incineration bottom ash is as follows:
[0062] Na2O:2.359%; MgO:2.116%; Al2O3:10.037%; SiO2:19.122%; P2O5:2.625%; SO3:2.393%; CaO:43.115%; Cl:0.166%; K2O:0.848%; Fe2O3:9.313%; C uO: 0.872%; TiO2: 2.48%; BaO: 0.239%; MnO: 0.196%; RbO: 0.317%; SrO: 0. 132%; Cr2O3: 0.15%; NiO: 0.042; ZnO: 1.287; ZrO2: 0.035%; Ag2O: 0.158%.
[0063] This embodiment also provides a method for preparing the green and environmentally friendly alkali-activated gelling material, which specifically comprises the following steps:
[0064] S1. Mix the waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash according to the above ratio, and mill them in a ball mill for a certain period of time so that the specific surface area of the admixture obtained after sufficient ball milling is greater than 600m 2 / kg;
[0065] S2. Mix the admixture with alkaline activator water glass according to the above ratio to obtain a cementitious material.
[0066] Examples 2 to 5 and Comparative Examples 1 to 5
[0067] Examples 2 to 5 and comparative examples 1 to 5 respectively provide a green and environmentally friendly alkali-activated gelling material. Compared with Example 1, the difference is that the composition of the gelling material is changed. The preparation method is the same as that of Example 1 and is not repeated here. For the convenience of comparison, the weight percentage of each raw material in the gelling material is used to represent the dosage of each raw material. The weight percentage of the raw materials corresponding to each example and comparative example is shown in Table 1.
[0068] Table 1 Weight percentage of each raw material in the gelling materials provided in Examples 2 to 5 and Comparative Examples 1 to 5
[0069]
[0070]
[0071] The working performance and mechanical properties of the cementitious materials prepared in Examples 2 to 5 and Comparative Examples 1 to 5 were tested. When the mechanical properties were tested, a mortar test was used, where the prepared cementitious materials and standard sand were mixed at a mass ratio of 1:3, and water was added at a water-cement ratio of 1:2, and naturally cured for 3 days, 7 days, and 28 days. The measured results are shown in Table 2.
[0072] Table 2 Properties of the cementitious materials prepared in Examples 2 to 5 and Comparative Examples 1 to 5
[0073]
[0074]
[0075] It can be seen from the above table that the mechanical properties of Examples 1, 4 and 5 are better; compared with Example 1, Example 2 increases the amount of waste granite powder and municipal solid waste incineration bottom ash while keeping the ratio between blast furnace slag and metakaolin unchanged, and reduces the amount of slag and metakaolin, and the overall mechanical properties are reduced; compared with Example 2, Example 3 replaces the alkaline activator from water glass to sodium hydroxide, and the mechanical properties are significantly reduced, indicating that the type of alkaline activator has an important influence on the cementitious material provided by the present invention.
[0076] In addition, compared with the embodiments, the mechanical properties of the comparative examples are relatively poor. Among them, comparative example 1 does not use an alkaline activator, it is difficult to create the required alkaline environment, the activity of each raw material cannot be effectively stimulated, and the strength of the obtained cementitious material is relatively low; the amount of blast furnace slag in comparative example 2 is small, resulting in slow performance growth of the cementitious material, and a long final setting time, which is easy to affect the construction progress; the amount of municipal solid waste incineration bottom ash in comparative example 3 is too high, which is not conducive to the growth of the strength of the cementitious material; the amount of waste granite powder in comparative example 4 is too small, which is not conducive to its large-scale recovery on the one hand, and on the other hand, it will cause the setting time to be too fast, which is not conducive to the casting and molding of concrete; the content of kaolin in comparative example 5 is low, and the strength of the cementitious material will also be reduced accordingly.
[0077] The present invention can effectively utilize the synergistic effect between the raw materials by controlling the amount of each raw material within a reasonable range. While adding a large amount of waste granite powder, the waste granite powder is used to improve the activation effect of kaolin and blast furnace slag, and to alleviate the expansion and deformation of the bottom ash from the incineration of municipal solid waste, thereby obtaining a green and environmentally friendly alkali-activated cementitious material with good working performance and high mechanical properties.
[0078] In summary, the present invention provides a green and environmentally friendly alkali-activated cementitious material and a preparation method thereof. The green and environmentally friendly alkali-activated cementitious material comprises the following components by mass fraction: 25.5% to 52% of waste granite powder, 16% to 37.5% of blast furnace slag, 10% to 27% of metakaolin, 10% to 20% of bottom ash from incineration of municipal solid waste, and 5% to 10% of alkaline activator. The waste granite powder, blast furnace slag, metakaolin and bottom ash from incineration of municipal solid waste are mixed according to the above proportions, and an admixture is obtained after sufficient ball milling, and the admixture is then mixed with an alkaline activator to obtain the above-mentioned cementitious material. In the above manner, the present invention can improve the utilization rate of solid waste materials while utilizing the synergistic effect between the solid waste materials, improve the performance of the cementitious material, and alleviate the expansion deformation of the bottom ash from incineration of municipal solid waste, so as to form a cementitious material with better working performance and higher mechanical properties.
[0079] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A green and environmentally friendly alkali-activated gelling material, characterized in that: The components are as follows by weight: 25.5-52 parts of waste granite powder, 16-37.5 parts of blast furnace slag, 10-27 parts of metakaolin, 10-20 parts of municipal solid waste incineration bottom ash, 5-10 parts of alkaline activator; The waste granite powder contains the following components by mass fraction: Na2O 6%~10%, MgO 0.2%~0.8%, Al2O3 15%~20%, SiO2 60%~70%, Fe2O3 1%~1.5%, K2O 4%~5%; The blast furnace slag contains the following components by mass fraction: Na2O 0.1%~0.5%, MgO 4%~8%, Al2O3 10%~20%, SiO2 20%~40%, SO3 1.5%~3%, CaO 30%~50%, K2O 0.5%~1%, Fe2O3 0.2%~0.6%, TiO2 0.6%~1.2%, MnO 0.5~1%; The metakaolin contains the following components by mass fraction: Na2O 0.02%~1%, MgO 0.1%~0.4%, Al2O3 40%~60%, SiO2 40%~60%, CaO 0.1%~0.5%; The municipal solid waste incineration bottom ash contains the following components by mass fraction: Na2O 1%~3%, MgO 1%~3%, Al2O3 5%~15%, SiO2 15%~25%, P2O5 1.5%~3.5%, SO3 1%~3%, CaO30%~50%, Fe2O3 6%~12%, TiO2 1.5%~35%.
2. The green and environmentally friendly alkali-activated gelling material according to claim 1, characterized in that: The alkaline activator is one of sodium hydroxide and water glass or a combination of the two.
3. A method for preparing a green and environmentally friendly alkali-activated gelling material according to any one of claims 1 to 2, characterized in that: The steps include: S1. Mixing waste granite powder, blast furnace slag, metakaolin and municipal solid waste incineration bottom ash according to a predetermined ratio, and fully ball-milling to obtain an admixture; S2. Mixing the admixture with the alkaline activator according to a predetermined ratio to obtain a gelling material.
4. The method for preparing the green and environmentally friendly alkali-activated gelling material according to claim 3, characterized in that: In step S1, the specific surface area of the admixture obtained after sufficient ball milling is greater than 600 m 2 / kg.
5. The method for preparing the green and environmentally friendly alkali-activated gelling material according to claim 3, characterized in that: After the cementitious material obtained in step S2 is mixed with standard sand and water and naturally cured, its 3d compressive strength is 4-12MPa, 7d compressive strength is 7-20MPa, 28d compressive strength is 8-35MPa, 3d flexural strength is 0.5-4MPa, 7d flexural strength is 1-5MPa, and 28d flexural strength is 1.5-6MPa.
6. The method for preparing the green and environment-friendly alkali-activated gelling material according to claim 5, characterized in that: The mass ratio of the cementitious material to the standard sand is 1:3, and the water-cement ratio of water to the cementitious material is 1:2.
Citation Information
Patent Citations
Method for preparing concrete by using high-mountain flour content granite chips
CN102887692A
Preparation process of alkali-activated cementing material for waste incineration bottom ash treatment
CN114315188A
Waste incineration bottom ash-based high-strength geopolymer plugging and filling material and preparation method thereof
CN114988769A